MAKNA SIMBOLIK GENDHING PATALON DALAM PERSPEKTIF RELIGIUSITAS ISLAM - Purwadi Purwadi (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
This research aims to describe gendhing patalon in Wayang (shadow puppet) Purwa related to the context of Islamic teachings. Hermeneutic method and theory are employed to explore this study object. Wayang Purwa is Javanese manifestation of collective reflection and contemplation, tafakur and tadzakur. Wayang Purwa, with its artistic values, has spiritual education or al-tarbiyah al-rabbaniyah and morality concepts or al-akhlaq al-karimah. The dalang (puppet master), wiyaga (gamelan musician) and waranggana (gamelan choir) believe this gendhing was created by Walisanga (the nine Islamic pioneers in Java). Dalang, with his central position in the show of Wayang Purwa ought to teach his audience to do righteous deeds or amal shalih. The sacred Gendhing patalon conveys a religious atmosphere, which gives mystical experiences to its audiences. By seeing the performance, the audience is expected to get the idea of the self essence - rasa jati or makrifat. It is called wikan sangkan paraning dumadi or ‘knowing the highest truth’. Wayang Purwa plays its role for young generation in moral education, character building, and national identity in this global era. Problems of life as well as the nation can be solved by local wisdom approach.